2015
DOI: 10.1186/s13601-016-0092-0
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and interpretation of skin prick test results

Abstract: BackgroundThere are several methods to read skin prick test results in type-I allergy testing. A commonly used method is to characterize the wheal size by its ‘average diameter’. A more accurate method is to scan the area of the wheal to calculate the actual size. In both methods, skin prick test (SPT) results can be corrected for histamine-sensitivity of the skin by dividing the results of the allergic reaction by the histamine control. The objectives of this study are to compare different techniques of quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 15 publications
0
77
0
Order By: Relevance
“…Postnatal questionnaires provided information on breastfeeding, day care attendance, lower respiratory tract infections and passive smoking in the first year. At the age of 10 years, inhalant allergic sensitisation for the five most common inhalant allergens (house dust mite, grass, birch, cat and dog) was determined by a skin prick test (ALK-Abelló, Almere, the Netherlands), using the ‘scanned area’ method 35. Length and weight at 10 years of age were measured and BMI (in kg/m 2 ) adjusted for age and sex was calculated 36…”
Section: Methodsmentioning
confidence: 99%
“…Postnatal questionnaires provided information on breastfeeding, day care attendance, lower respiratory tract infections and passive smoking in the first year. At the age of 10 years, inhalant allergic sensitisation for the five most common inhalant allergens (house dust mite, grass, birch, cat and dog) was determined by a skin prick test (ALK-Abelló, Almere, the Netherlands), using the ‘scanned area’ method 35. Length and weight at 10 years of age were measured and BMI (in kg/m 2 ) adjusted for age and sex was calculated 36…”
Section: Methodsmentioning
confidence: 99%
“…To increase the accuracy of the SPT, the area of the allergen-induced wheal can be compared with the area of a histamine-induced wheal size (as positive control) to correct for skin histamine sensitivity. The ratio is defined as histamine equivalent prick (HEP) index [34]. Considering an average wheal diameter over 3 mm and HEP index area ≥0.4 as baseline for positive sensitization, van der Valk et al [32] reported a mean value of 3.02 of HEP index (range 0-15.16) in 164 of cashew nut allergic children.…”
Section: Diagnosis Therapy and Immunotherapymentioning
confidence: 99%
“…cashew nut) and/or to confirm the allergy [28]. In general, individuals presenting a convincing medical history of cashew nut allergy, SPT of wheal diameter over 3 mm (HEP index ≥0.4) and/or serum-specific IgE of 0.35 kUA/L are often purposed for oral provocation tests (DBPCFC or OFC) with increasing doses of cashew nut [32,34]. The oral provocation tests are normally discontinued and considered positives when objective symptoms occur, when severe subjective symptoms persist (>1 h) or when subjective symptoms re-appear after second dose of the same challenge material [32].…”
Section: Diagnosis Therapy and Immunotherapymentioning
confidence: 99%
“…22 We measured inhalant allergic sensitization by skin prick test using the "scanned area method", 23 for which detailed information is provided in the Appendix S1. Maternal weight and height were measured at enrollment.…”
Section: Covariatesmentioning
confidence: 99%
“…The country of birth of parents was used to define the child's ethnicity. 22 We measured inhalant allergic sensitization by skin prick test using the "scanned area method", 23 for which detailed information is provided in the Appendix S1.…”
Section: Covariatesmentioning
confidence: 99%